Computer Presentation Programs and Teaching Research Methodologies - Vahid Motamedi (Intelektual Pustaka Media Utama, 2015)
Supplementing traditional chalk and board instruction with computer delivery has been viewed positively by students who have reported increased understanding and more interaction with the instructor when computer presentations are used in the classroom. Some problems contributing to student errors while taking class notes might be transcription of numbers to the board, and handwriting of the instructor can be resolved in careful construction of computer presentations. The use of computer presentation programs promises to increase the effectiveness of learning by making content more readily available, by reducing the cost and effort of producing quality content, and by allowing content to be more easily shared. This paper describes how problems can be overcome by using presentation packages for instruction.